Distribution channel choice of international born digital companies : International digital solution provider companies - Mäkelä, Jani (My University, 2021)
Many countries are increasingly digitalizing, and the share of digital companies is also concurrently increasing across economies. Particularly the phenomenon of born digital companies is becoming more and more widespread. However, these companies fully digital from the inception have so far only relatively recently gained more research attention. Therefore, also the effect of their digital product portfolios and value chains on sales and distribution channel strategies have arguably remained a less researched topic. Thus, further understanding on this topic is provided by answering the research question of how born digital companies should organize their international distribution. This question is answered by first surveying which channels born digital companies are utilizing and why these have been chosen. Furthermore, besides other factors, the effects of digital product and service as well as highly digitalized value chain on distribution channel are examined to offer more understanding on this question. The thesis is a qualitative study based on semi-structured interviews as well as online sources. Online materials such as company websites were used to gather data both before and after the interviews. These empirical findings on the companies were then contrasted with previous research. The analysis resulted in both findings that supported some of the previous research as well as some new findings. The findings supported the notion of previous research that digital business model often allow born digital companies to bypass many physical barriers. In other words, digital value chains tend to reduce the role of intermediaries. Therefore, avoiding intermediaries and instead applying more direct channels is often easier even in foreign markets. Many born digital companies seem to also prefer to keep their core knowhow and competency in-house, which discourages overreliance on intermediaries. However, despite less burden of physical constraints, born digital companies are still faced with challenges posed by culture and other institutional factors. In other words, phenomena such as psychic distance and liability of outsidership remain significant even in digital business environment and have an effect on distribution channel strategies of born digital companies. Nonetheless, despite intermediaries and other indirect channels also being used, the main focus of digital solution providing born digital companies is often on developing own direct channels.

Maailma digitalisoituu nykyään nopeasti ja näin ollen samoin kasvaa myös digitaalisten yritysten määrä monissa talouksissa. Erityisesti niin kutsuttujen born digital -yritysten ilmiö on yleistymässä. Tästä huolimatta näitä alusta alkaen täysin digitaalisia yrityksiä on ryhdytty tutkimaan enenevissä määrin vasta viime aikoina. Tämän takia myös näiden yritysten digitaalisten tuoteportfolioiden ja arvoketjujen vaikutusta myynti- ja jakelukanavastrategioihin on tutkittu toistaiseksi melko rajallisesti. Näin ollen aihealueen tuntemusta syvennetään tässä tutkimuksessa tutkimalla, miten born digital -yritysten tulisi organisoida kansainväliset jakelukanavansa. Aluksi tarkastellaan mitä kanavia kyseiset yritykset hyödyntävät ja miksi näihin kanaviin on päädytty. Lisäksi muiden tekijöiden ohella tarkastellaan digitaalisten tuotteiden ja palveluiden sekä digitaalisten arvoketjujen vaikutusta valintaan. Tutkielma on luonteeltaan kvalitatiivinen ja pohjautuu puolistrukturoituihin haastatteluihin sekä verkkolähteisiin. Tietoja yrityksistä kerättiin sekä ennen että jälkeen haastatteluita verkkolähteistä kuten yritysten kotisivuilta. Kerättyjä empiirisiä tuloksia verrattiin aikaisempiin tutkimuksiin. Analyysin pohjalta tehdyt havainnot osaltaan sekä tukivat joitakin aikaisempia havaintoja että nostivat esiin joitakin uusia löydöksiä. Tutkimustulokset tukivat aikaisempia havaintoja, joiden mukaan digitaaliset liiketoimintamallit usein mahdollistavat joidenkin liiketoiminnan fyysisten esteiden ohittamisen. Tällöin suorien kanavien hyödyntäminen välikäsien sijaan kansainvälisillä markkinoilla usein helpottuu. Digitaaliset arvoketjut myös vähentävät välikäsien merkitystä. Lisäksi monet born digital -yritykset haluavat pitää ydinosaamisensa ja -tietotaitonsa yrityksen sisällä eivätkä tällöin halua olla näiden suhteen liian riippuvaisia ulkopuolisista välikäsistä. Fyysisten rajoitteiden vähentymisestä huolimatta digitaalisia yrityksiä rajoittavat kuitenkin yhä kulttuurin ja muiden institutionaalisten tekijöiden haasteet. Toisin sanoen ilmiöt kuten henkinen etäisyys (eng. ’psychic distance’) ja ulkopuolisuuden taakka (eng. ’liability of outsidership’) säilyvät yhä merkittävinä tekijöinä myös digitaalisessa liiketoimintaympäristössä ja näin vaikuttavat yhä myös kanavavalintoihin. Toisin sanoen välikäsiä ja muita epäsuoria kanavia hyödynnetään yhä, mutta pääfokus digitaalisia ratkaisuja tarjoavilla yrityksillä on kuitenkin omien suorien kanavien kehittämisessä.
Keywords: Born digital firms, Distribution channel choice, Digital solution providers